Rancang Bangun Prototype Sistem Pendeteksi Jumlah Kendaraan Bermotor Menggunakan Sensor Ultrasonik Dan Load Cell Berbasis Mikrokontroler - Achmad Yanuar Ramadhani; Nur Kasan; Widianto Widianto (Journal of Mechatronic and Electrical Engineering, 2021)
Parking is a temporary stop that has been provided for types of vehicles. Along with the development of increasingly modern times, the use of private cars as a means of transportation has become commonplace. Private vehicle users who want to park are not well informed about the state of the parking area. Because there is no information about the availability of empty parking spaces. With a system that provides information on the entry and exit of vehicles, it is hoped that it can help and provide solutions to motorists in finding locations that are still empty. For the parking lot provider it makes it easy to take action with an information system regarding the number of entries and exits if the parking lot is full using the Karnaugh-map method. The results of the load cell sensor calibration using the linear regression method were successful, the R value was 1 and Sx was 9%. From the classification of motorbikes and cars, each consists of light, medium and heavy ultrasonic sensor programming successfully calculates and differentiates the number of vehicles between motorbikes and cars by using the selection.